Experimental Carbonic Anhydrase Inhibitors for the Treatment of Hypoxic Tumors - Supuran CT (Dove Medical Press, 2020)
Claudiu T Supuran Neurofarba Department, Pharmaceutical and Nutraceutical Section, University of Florence, Florence 50019, ItalyCorrespondence: Claudiu T SupuranNeurofarba Department, Pharmaceutical and Nutraceutical Section, University of Florence, Via Ugo Schiff 6, Sesto Fiorentino, Florence 50019, ItalyEmail claudiu.supuran@unifi.itAbstract: Carbonic anhydrase (CA, EC 4.2.1.1) isoforms IX and XII are overexpressed in many hypoxic tumors as a consequence of the hypoxia inducible factor (HIF) activation cascade, being present in limited amounts in normal tissues. These enzymes together with many others are involved in the pH regulation and metabolism of hypoxic cancer cells, and were validated as antitumor targets recently. A multitude of targeting strategies against these enzymes have been proposed and are reviewed in this article. The small molecule inhibitors, small molecule drug conjugates (SMDCs), antibody-drug conjugates (ADACs) or cytokine-drug conjugates but not the monoclonal antibodies against CA IX/XII will be discussed. Relevant synthetic chemistry efforts, coupled with a multitude of preclinical studies, demonstrated that CA IX/XII inhibition leads to the inhibition of growth of primary tumors and metastases and depletes cancer stem cell populations, all factors highly relevant in clinical settings. One small molecule inhibitor, sulfonamide SLC-0111, is the most advanced candidate, having completed Phase I and being now in Phase Ib/II clinical trials for the treatment of advanced hypoxic solid tumors.Keywords: carbonic anhydrase, hypoxia, inhibitor, small molecule drug conjugates, anticancer drug, SLC-0111